Ship entering floating dock Chaguaramas Bay - (:unkn) unknown (Stephens Ltd., [Trinidad and Tobago], 2011)
This postcard shows a ship entering a floating dock on Chaguaramas Bay, Trinidad. Floating docks are used to construct or carry out maintenance or repairs on any type of watercraft such ships or boats.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Dry docks; Ships